Discovery of Novel DENN Proteins: Implications for the Evolution of Eukaryotic Intracellular Membrane Structures and Human Disease - Zhang, Dapeng; Iyer, Lakshminarayan M.; He, Fang; Aravind, L (Frontiers in Genetics, 2012)
The tripartite DENN module, comprised of a N-terminal longin domain, followed by DENN and d-DENN domains, is a GDP-GTP exchange factor (GEFs) for Rab GTPases, which are regulators of practically all membrane trafficking events in eukaryotes. Using sequence and structure analysis we identify multiple novel homologs of the DENN module, many of which can be traced back to the ancestral eukaryote. These findings provide unexpected leads regarding key cellular processes such as autophagy, vesicle-vacuole interactions, chromosome segregation and human disease. Of these, SMCR8, the folliculin interacting protein-1 and 2 (FNIP1 and FNIP2), nitrogen permease regulator 2 (NPR2) and NPR3 are proposed to function in recruiting Rab GTPases during different steps of autophagy, fusion of autophagosomes with the vacuole and regulation of cellular metabolism. Another novel DENN protein identified in this study is C9ORF72; expansions of the hexanucleotide GGGGCC in its first intron have been recently implicated in amyotrophic lateral sclerosis (ALS) and fronto-temporal dementia (FTD). While this mutation is proposed to cause a RNA-level defect, the identification of C9ORF72 as a potential DENN-type GEF raises the possibility that at least part of the pathology might relate to a specific Rab-dependent vesicular trafficking process, as has been observed in the case of some other neurological conditions with similar phenotypes. We present evidence that the longin domain, such as those found in the DENN module, are likely to have been ultimately derived from the related domains found in prokaryotic GTPase-activating proteins of MglA-like GTPases. Thus, the origin of the longin domains from this ancient GTPase-interacting domain, concomitant with the radiation of GTPases, especially of the Rab clade, played an important role in the dynamics of eukaryotic intracellular membrane systems.